2017
DOI: 10.1165/rcmb.2015-0255oc
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 Controls the Myofibroblastic Differentiation of Bronchial Fibroblasts from Patients with Asthma

Abstract: Pathologic accumulation of myofibroblasts in asthmatic bronchi is regulated by extrinsic stimuli and by the intrinsic susceptibility of bronchial fibroblasts to transforming growth factor-β (TGF-β). The specific function of gap junctions and connexins in this process has remained unknown. Here, we investigated the role of connexin43 (Cx43) in TGF-β-induced myofibroblastic differentiation of fibroblasts derived from bronchoscopic biopsy specimens of patients with asthma and donors without asthma. Asthmatic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(90 citation statements)
references
References 41 publications
6
74
2
Order By: Relevance
“…Close associations of GC with the growth factor‐producing activity of organ‐specific fibroblasts have already been reported . Numerous reports indicate that this kind of reactions is common for cancer‐predisposed fibroblasts . Notably, in our experimental model the expression of Snail mRNA was upregulated in Hp ‐infected fibroblasts.…”
Section: Discussionsupporting
confidence: 64%
“…Close associations of GC with the growth factor‐producing activity of organ‐specific fibroblasts have already been reported . Numerous reports indicate that this kind of reactions is common for cancer‐predisposed fibroblasts . Notably, in our experimental model the expression of Snail mRNA was upregulated in Hp ‐infected fibroblasts.…”
Section: Discussionsupporting
confidence: 64%
“…However, only NA HBFs in the mixed TGF-β1 treated EMTU cultures showed a significant protective effect of HBFs on the epithelial layer permeability (measured as the TEER value). A similar protective effect of fibroblasts on the TEER values was described previously in co-cultures of HBECs with MRC5 cells in the EMTU model compared to equivalent HBEC monocultures[49].Longitudinal studies on the TGF-β1-induced FMT potential (a key event in asthmatic subepithelial fibrosis) revealed a facilitated ability of asthmatic HBF populations in standard '2D' cultures for phenotypic shifts[23,25,27,28,50], that may indicate the involvement of intrinsic properties of these cells on the regulation of FMT. In this study, we also observed the enhanced FMT potential defined by a relatively high level of ACTA2 (encodes α-SMA), TAGLN…”
supporting
confidence: 53%
“…Our longitudinal studies clearly show that populations of the AS and NA HBF cultured in the identical conditions in a serum-free medium display different features affecting their sensitivity to the external TGF-β1 and FMT potential. In standard in vitro cultures the AS HBFs in response to the TGF-β1 develop the myofibroblastic phenotype characterized by a relatively high level of α-SMA incorporated into stress fibers more efficiently than the NA counterparts [23- 25,27,28]. To clarify whether this phenomenon is pronounced in the EMTU co-cultures, we firstly checked in this study if the medium dedicated for the air-liquid-interface (ALI) and EMTU cultures significantly affects the FMT potential of the TGF-β1-treated HBFs.…”
Section: Ali Medium Does Not Change the Profibrotic Properties Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate consequence of the TGF-β signalling is transcriptional dysregulation of target genes which control cell proliferation and production of structural and ECM proteins, such as collagens, laminins, fibronectin and many others (Branton & Kopp, 1999). TGF-β-dependent mechanisms contribute to fibrotic processes not only in the heart, but also in other organs, including kidney, liver, lung or skeletal muscle (Biernacka et al, 2011;Dooley & ten Dijke, 2012;Germano et al, 2009;Leask, 2007;Meng et al, 2015;Paw et al, 2017;Tatler & Jenkins, 2012, Li et al, 2004.…”
Section: Tgf-β-dependent Signalling Pathways In Cardiac Fibrosismentioning
confidence: 99%